Between a Rock and Hard Place: Combined Effects of Authentic Leadership, Organizational Identification, and Team Prototypicality on Managerial Prohibitive Voice. (1st March 2019) - Monzani, Lucas; Knoll, Michael; Giessner, Steffen; van Dick, Rolf; Peiró, José María
Abstract: Managers are installed by the organization's stakeholders and shareholders to increase the organization's value; at the same time, they depend on their subordinates' acceptance to fulfill this leadership role. If the interest of the organization collides with the interest of their team, some managers act in the interest of their followers accepting potential disadvantages for their organizations and/or external stakeholders. In two experimental studies comprised mainly of German ( N = 111) and US ( N = 323) managers, we examined combined effects of authentic leadership, organizational identification, and self-perceived team prototypicality on managerial integrity operationalized as expressing work-related concerns to prevent organizations from harm (i.e., managerial voice). Our results show direct effects of authentic leadership and organizational identification on voice behavior across both studies. Furthermore, organizational identification increased voice for managers' low in authentic leadership pointing at a compensation effect. Finally, leader team prototypicality decreased the effect of identification on voice for managers high in authentic leadership but increased voice for managers low in authentic leadership, but only if these managers identified with their organization. In sum, our findings complement prior research that focused mainly on safety and instrumentality concerns by emphasizing the relevance of self-related antecedents of managerial voice.